PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAk) DI FAKULTAS EKONOMI & BISNIS UNIVERSITAS BRAWIJAYA MALANG - Nur Eka Yanti; Nur Hidayati; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRAKThis study aims to determine the effect of career, degree, economic andquality motivation on the interest of accounting students to take the accountingprofession education exam (PPAK). This study took a sample by distributingquestionnaires to students of the Faculty of Economics and Business, Universityof Brawijaya Accounting Study Program. The sampling technique uses purposivesampling. The data processed in this study were 73 respondents. The results of thestudy show that career, degree, economic and quality motivations simultaneouslyinfluence the interest in taking part in the accounting profession education(PPAK). Career, economic and quality motivation has a partial effect on theinterest in taking part in the accounting profession education (PPAK), while thedegree motivation does not affect the interest in taking part in the accountingprofession education (PPAK).Keywords: Career motivation, degree, economy, quality, interest in accountingprofession education (PPAK)